EXPLORATION OF ONLINE DISCUSSION FORUM ON READING EST TEXTS FOR ESL LEARNERS (Malaysian Journal of Learning and Instruction, 2022)
Purpose: This study explored ESL learners’ utilization of Online Discussion Forums (ODFs) in Interactive Reading for Academic Disciplines (iREAD) to assist reading of online scientific texts within an English for Specific Purposes course at a public university.Method: This qualitative research employed two data collection methods during lessons of a 14-week semester. The first was analysis of ODF threads in iREAD from 30 ESL learners of various engineering programs at a public university in the East coast of Malaysia. Twelve from 30 ESL students were purposively selected to participate in focus group interviews. Interactive Analysis Model was used to analyse the threads, whilst the interviews transcripts were analysed thematically. NVivo Pro 12 software was used to manage the data and the generated themes were later analysed using inter-rater reliability analysis. The Kappa values of the themes indicated near perfect scores, to verify the reliability of the identified themes.Findings: The findings revealed the positive capability of ODF as a tool in facilitating learners’ reading comprehension of English for Science and Technical (EST) online materials. Analysis of the data on ODF threads confirm that students have the capabilities to engage in higher level of discussions and debate to aid their understanding. The themes that emerged from the interviews reflect positive impacts to facilitate reading of EST online materials, where learners were able to work collaboratively and increase knowledge and understand better. In addition, significance of EST materials was important in providing exposure to students’ background knowledge of their content courses. The notion of social constructivism and connectivism were reflected as learners constructed knowledge, negotiated, and synthesized ideas using the language across networked learning communities.Significance: An implication from this study suggests that exposure to EST online materials through communication and collaboration via ODF has strengthened students’ knowledge of the subject content. Additionally, learners’ comprehension of reading online EST materials has been enhanced through ODF because of the tool’s interactive heuristic approach to learning. This becomes significant for program developers and lecturers to combine both elements of ODF and material selection in lessons considering its positive impacts toward learning.